Huddling behaviour and energetics of Sminthopsis spp. (Marsupialia, Dasyruidae) in response to environmental challenge - Tomlinson, Sean; Withers, Philip; Maloney, S. (2014)
We describe how behavioural responses are an important adjunct to physiological responses for two dunnart marsupials that live in arid environments. Behavioural responses of the stripe-faced dunnart Sminthopsis macroura and the Ooldea dunnart Sminthopsis ooldea differed with acclimation to four ambient temperature (Ta) regimes, 12h:12h of 5-15°C, 12-22°C, 18-28°C and 25-35°C. Aggression levels were low at regimes 5-15°C and 12-22°C, and high at regimes 18-28°C and 25-35°C. The proportion of S. macroura huddled in groups increased significantly with decreasing Ta regime, but there was no aggregation by S. ooldea at low Ta regimes. The energetic benefit of huddling by S. macroura was highest for pairs of dunnarts (27% saving compared with singles) and only 3% for triplets at Ta=10°C. Thermal conductance decreased for pairs but not triplets compared to singles. There were no energetic savings for S. ooldea with increased numbers, and thermal conductance was the same per individual for single, pairs and triplets, reflecting their lack of huddling behaviour. The flexible behavioural (huddling) responses of S. macroura may facilitate their capacity to occupy a broad geographical distribution, unlike S. ooldea, which had inflexible behavioural responses (no huddling) and has a more restricted geographical range. The phylogenetic relationships of the dunnarts suggest that social behaviours may have arisen only once in the most adaptable subgroup of the Sminthopsini. © 2014.